2х - 3у + 4х + 3у = 9+27
6х = 36
х = 36:6
х = 6
2*6 - 3у = 9
12 - 3у = 9
3у = 12 - 9
3у = 3
у=1
Ответ: х=6, у=1
4)
Второе уравнение умножаем на 4 и получаем:
4*(2х-у) = 4*15
8х -4у = 60 - теперь можно прибавить первое уравнение
8х - 4у + х + 4у = 39 + 60
9х = 99
х = 11
11 + 4у = 39
4у = 39 - 11
4у = 28
у = 28:4
у=7
Ответ: х = 11, у =7
Ответ:
а) 2.85
б) 20.5/11.
Решение :
а) -1,14*(-2,5)= 2,85
б) -41/12 * (-6/11) = -41/12 * (- 1/11) = 20.5/11
1) х : 7 = 12 2) 56: у = 8 3) х + 5 : 21 = 10
18+7=25
27+6=33
(40-23)+3=20
(90-65)+7=32
(46+6)- 20=32
(79+3)-30=52
<span>(3x-2)/(2-x)>-2 *2-х; хне равен 2
3х-2>-4+2х
3х-2х>-4+2
х>-2
Ответ:от -1 до +бесконечности
</span>